APAKAH FLYPAPER EFFECT TERJADI DI ACEH? STUDI MENGUKUR KEMANDIRIAN KEUANGAN DAERAH - Muhammad Hasan Basri (Universitas Negeri Medan, 2014)
The objective of this study is to analyse the phenomenon of flypaper effect in Aceh after the implementation of fiscal decentralization. Data used in the study were panel data covering all 23 district/municipalities in Aceh from 2011 to 2013. Pooled Least Square was utilized. The results of this study revealed that ownsource revenue, sharing revenue, special allocation funds, general allocation funds, and special autonomy funds are statistically significant variables and have a positive relation to regional spending. It was proven that flypaper effect has occured in Aceh as the coefficient of the own-source revenue variabel was smaller than that of sharing revenue variabel. This implied that Aceh has been dependent on the national government in term of regional financing. Based on descriptive analysis, provinces having dominant share of tertiary sector to their regional gross domestic products show fiscally independent. In order to achieve fiscal independence, the phenomenon of flypaper effect could be overcomed by shifting the economic structure from the primary and secondary to the tertiary sectors of the economy. In doing so, the contribution of own-source revenue to regional spending outweigh intergovernment transfer funds from national government.